(untitled) (Bangladesh Journal of Anatomy, 2011)
Context: Cisplatin, an effective antineoplastic agent, is the drug of choice in the treatment of germ cell tumours. It is one of the important nephrotoxic drugs. Oxidative stress is suggested to be a significant contributor to cisplatin-induced nephrotoxicity. So, vitamin C and spirulina having antioxidant properties are expected to deal with the situation. The study was designed to observe the effects of vitamin C and spirulina on cisplatin-induced interstitial nephritis in Long Evans rats. Study design: Experimental Place and period of study: Department of Anatomy, Sir Salimullah Medical College, Dhaka, from September, 2005 to December, 2006. Materials and Methods: Forty adult Long Evans rats, of either sex, weighing 220-300 gms each, were divided into four equal batches depending on the drug treatment they received: (a) ’normal control’ – distilled water and normal saline, (b) ’experimental control’ – cisplatin, (c) ’vitamin C treated’ – cisplatin plus vitamin C, and (d) ’spirulina treated’ – cisplatin plus spirulina. Histologically, nephrotoxicity was determined by the presence of inflammatory changes in the interstitium. Results: Nephrotoxic control rats showed marked interstitial nephritis as evidenced by histological features. Pretreatment with either vitamin C or spirulina reduced the cisplatin-induced interstitial nephritis (p<0.001), while spirulina was more effective than vitamin C as evidenced histologically (P< 0.001). Conclusion: It can be concluded from this study that both spirulina and vitamin C have preventive impact on cisplatin-induced interstitial nephritis in rats. Key words: Cisplatin; interstitial nephritis; vitamin C; spirulina DOI: 10.3329/bja.v8i2.7014 Bangladesh Journal of Anatomy July 2010, Vol. 8 No. 2 pp. 47-51